2017
DOI: 10.3892/ijo.2017.4057
|View full text |Cite
|
Sign up to set email alerts
|

Nestin-positive microvessel density is an independent prognostic factor in breast cancer

Abstract: The process of angiogenesis based on new vessel formation within the tumour area plays a significant role in the progression of breast cancer. Nestin is an intermediate filament protein and participates in the cytoskeleton organization. Nestin expression in the endothelium of blood vessels is mainly limited to newly forming vessels, thus being a more specific marker of angiogenesis than the commonly used vascular antigens. The aim of this study was to determine the prognostic value of nestin-positive microvess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Therefore, we compared nestin expression to the area and number of vessels expressing the vascular antigens, nestin, (21,(37)(38)(39). Our previous study indicated that in BC, nestin is a valuable marker of newly-forming tumour vessels and reflects ongoing angiogenesis (21). In the present study, we demonstrated that nestin expression in tumour cells correlated with the area and number of vessels expressing all investigated antigens i.e., nestin, CD31, CD34 and SOX-18.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…Therefore, we compared nestin expression to the area and number of vessels expressing the vascular antigens, nestin, (21,(37)(38)(39). Our previous study indicated that in BC, nestin is a valuable marker of newly-forming tumour vessels and reflects ongoing angiogenesis (21). In the present study, we demonstrated that nestin expression in tumour cells correlated with the area and number of vessels expressing all investigated antigens i.e., nestin, CD31, CD34 and SOX-18.…”
Section: Discussionsupporting
confidence: 58%
“…In our study, we also aimed to determine whether nestin expression in BC cells may be associated with the formation of new tumour vessels. Therefore, we compared nestin expression to the area and number of vessels expressing the vascular antigens, nestin, (21,(37)(38)(39). Our previous study indicated that in BC, nestin is a valuable marker of newly-forming tumour vessels and reflects ongoing angiogenesis (21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations